Optimisation of Transition Areas between Ballastless Track and Ballasted Track in the Area of the Tunnel Turecky Vrch - Izvolt, Libor; Harusinec, Jozef; Smalo, Michal (Communications - Scientific letters of the University of Zilina, 2018)
The paper follows previously published papers in Communications – Scientific Letters of the University of Zilina No. 4/2014, No. 4/2015 and No. 4/2016, where were presented the results of the diagnostics of the track geometry of the experimental sections surrounding the portals of a new building of the Tunnel Turecky vrch. Based on the data obtained by comprehensive diagnostics, there can be stated that the problematic section in the slab track are the transition areas allowing the transfer of the vehicle between the line structures with a different bending stiffness. The comprehensive diagnostics was realised by the continuous method (measuring trolley KRAB), the results of which were verified by the results of the measuring car of ZSR and by the geodetic monitoring of the layout of the track, as well. Mathematical modelling of the transition areas was realized in the environment of the software ANSYS with the aim to optimise the structural solution of the existing transition areas, as well as of in the future built ones, within the modernization of the railway infrastructure of the Slovak Republic. The model of the existing transition area was structurally optimised –models were realised with application of the stiffening rails and with usage of the under sleeper pads. The model of the current state and the models of the optimised structural solutions of the transition areas were subsequently compared by the values of the vertical displacement, vertical speed and vertical acceleration.